Trans-esterification of pangansius hypolatamus tallow waste with ethanol by electrolysis process and KO0H as catalyst - Bazlina Dawami Afrah; Muhammad Rendana; Muhammad Yori Pratama; Tiara Maharani Ramona Putri; Nurulia Rahmadianti; Dina Sabrina (Universitas Lambung Mangkurat, 2025)
Consumption of fuel energy continues to increase every year. Still, the fuel used today is almost entirely derived from fossil materials that are toxic to the environment and not renewable, so they need renewability to be guaranteed. One solution to this problem is ethyl ester based on catfish (Pangasius Hypothalamus) tallow waste. The catfish fish tallow is extracted first and then in a liquid phase and then reacted with the help of a KOH catalyst (1%; 1.5%; 2%) by electrolysis method using copper electrodes with a transesterification reaction. The research was conducted on the ratio of raw materials to ethanol of 1:5, 1:6, and 1:7 with a power supply voltage of 20V. It can be seen from the research results that the mole ratio of raw material and ethanol at 1:6 produces ethyl esters with a tendency to be of better quality. The best ethyl ester yield was obtained at a ratio of 1:6 raw material and 1.5% catalyst amount, and the resulting yield was 92.4058%.